Noninvasive ventilation technologies and healthcare for geriatric patients - Fonseca, César, 1973-; Lopes, Manuel José; Mendes, David, 1966-; Garcia-Alonso, José; Mendes, Felismina R. P. (Advances in medical diagnosis, treatment, and care (AMDTC) book series., 2020)
"This book explores noninvasive ventilation technologies and healthcare for geriatric patients"--